Psychological Flexibility and Mindfulness Explain Intuitive Eating in Overweight Adults. (July 2015) - Sairanen, Essi; Tolvanen, Asko; Karhunen, Leila; Kolehmainen, Marjukka; Järvelä, Elina; Rantala, Sanni; Peuhkuri, Katri; Korpela, Riitta; Lappalainen, Raimo
The current study investigated whether mindfulness and psychological flexibility, independently and together, explain intuitive eating. The participants were overweight or obese persons ( N = 306) reporting symptoms of perceived stress and enrolled in a psychological lifestyle intervention study. Participants completed self-report measures of psychological flexibility; mindfulness including the subscales observe, describe, act with awareness, non-react, and non-judgment ; and intuitive eating including the subscales unconditional permission to eat, eating for physical reasons, and reliance on hunger/satiety cues . Psychological flexibility and mindfulness were positively associated with intuitive eating factors. The results suggest that mindfulness and psychological flexibility are related constructs that not only account for some of the same variance in intuitive eating, but they also account for significant unique variances in intuitive eating. The present results indicate that non-judgment can explain the relationship between general psychological flexibility and unconditional permission to eat as well as eating for physical reasons . However, mindfulness skills— acting with awareness, observing, and non-reacting —explained reliance on hunger/satiety cues independently from general psychological flexibility. These findings suggest that mindfulness and psychological flexibility are interrelated but not redundant constructs and that both may be important for understanding regulation processes underlying eating behavior.